2021
DOI: 10.15408/jkv.v7i2.22158
|View full text |Cite
|
Sign up to set email alerts
|

Application of Fourier Transform Infrared Spectrophotometry Method for Analysis of Metformin Hydrochloride in Marketed Tablet Dosage Form

Abstract: The first line drug given for monotherapy for diabetes mellitus type 2 is metformin hydrochloride, which is a biguanide antihyperglycemic drug. The aim of this research was to develop, validate, and apply the Fourier Transform Infrared spectrophotometry method to identify and determine metformin hydrochloride in marketed tablet dosage form. This research included preparation of standard, analysis of samples, and validation of method. The specific wavenumber obtained for qualitative analysis was 1645.68 cm–1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Its richness in minerals and vitamins has made it an essential human diet alkaloids. 26 Published literature revealed that VA contains loads of phytochemicals and may be toxic at high doses. 27 More than thirty secondary metabolites belonging to different classes with varying bioactivities have been isolated and characterised from VA: sesquiterpene lactones, steroidal saponins, glycosides, flavonoids, and fatty acids and alkaloids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its richness in minerals and vitamins has made it an essential human diet alkaloids. 26 Published literature revealed that VA contains loads of phytochemicals and may be toxic at high doses. 27 More than thirty secondary metabolites belonging to different classes with varying bioactivities have been isolated and characterised from VA: sesquiterpene lactones, steroidal saponins, glycosides, flavonoids, and fatty acids and alkaloids.…”
Section: Resultsmentioning
confidence: 99%
“…27 More than thirty secondary metabolites belonging to different classes with varying bioactivities have been isolated and characterised from VA: sesquiterpene lactones, steroidal saponins, glycosides, flavonoids, and fatty acids and alkaloids. 26 In order to investigate how the continuous crude oil spills in Kokori affect VA, a quantitative ethnobotanical survey was performed following an interview of 82 respondents from Kokori and Abraka (Table 1).…”
Section: Resultsmentioning
confidence: 99%